2016
DOI: 10.18632/oncotarget.14396
|View full text |Cite
|
Sign up to set email alerts
|

Dual inhibition of PCDH9 expression by miR-215-5p up-regulation in gliomas

Abstract: The clinical prognosis of malignant gliomas is poor and PCDH9 down-regulation is strongly associated with its poor prognosis. But the mechanism of PCDH9 down-regulation is unknown. Abnormal miRNAs profiles regulate tumor phenotypes through inhibiting their target genes and miRNAs could inhibit target genes more efficiently by binding to both the promoter and 3′UTR of target genes. In this study, to search the dual inhibitory miRNAs which suppress PCDH9 expression in gliomas, we performed an integrative analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 36 publications
5
23
0
Order By: Relevance
“…These findings were consistent with the previous report, in which miR-215-5p inhibits the progression of colon cancer by modulating epidermal growth factor receptor ligand and Homeobox protein Hox-B9 [20]. In contrast, miR-215-5p had the potential of inhibiting the mRNA and the protein expression of Protocadherin-9 in glioma cells through regulating its promoter and 3'-UTR [21]. The luciferase reporter gene assay and western blotting assay demonstrated that Sox9 is the potential target of miR-215-5p in breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…These findings were consistent with the previous report, in which miR-215-5p inhibits the progression of colon cancer by modulating epidermal growth factor receptor ligand and Homeobox protein Hox-B9 [20]. In contrast, miR-215-5p had the potential of inhibiting the mRNA and the protein expression of Protocadherin-9 in glioma cells through regulating its promoter and 3'-UTR [21]. The luciferase reporter gene assay and western blotting assay demonstrated that Sox9 is the potential target of miR-215-5p in breast cancer.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that miR-215-5p is a tumor suppressor in colorectal cancer and upregulation of miR-215-5p inhibited cell proliferation of glioma. 21,22 Our findings suggested that miR-215-5p expression was markedly upregulated in the BM specimens as well as cell lines of MM compared to that in HD ( Figure 1A,B), suggesting that miR-215-5p might exert a vital part in MM development. Kaplan-Meier curves indicated that there was no difference in survival rate between miR-215-5p high expression group and miR-215-5p low expression group ( Figure 1C).…”
Section: Discussionmentioning
confidence: 71%
“…PCDH9 was identified as the downstream target of miR-215-5p in gliomas and inhibited the growth of glioma cells. 35 In this study, the possible binding sites of miR-200a-3p at the 3ʹ-UTR of PCDH9 was predicted with the miRDB. Functional analysis showed that miR-200a-3p bound the 3ʹ-UTR of PCDH9 and suppressed the expression of PCDH9 in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies demonstrated that PCDH9 was down-regulated in cancers, such as glioblastoma, hepatocellular carcinoma and gastric cancer. [35][36][37][38] Overexpression of PCDH9 inhibited the proliferation, migration and invasion of cancer cells. However, the function of PCDH9 in ovarian cancer remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%